2018
DOI: 10.15173/glj.v9i3.3712
|View full text |Cite
|
Sign up to set email alerts
|

Class Power and Union Capacities: A Research Note on the Power Resources Approach

Abstract: Arguably, the power resources approach (PRA) is the most elaborate and most significant attempt to establish a methodology for labour studies in recent years. It provides a toolkit for identifying sources of workers' power in capitalist societies. In my view, it has two particular strengths. First of all, it enables labour scholars to conduct strategic research that can help labour activists and trade unionists in their day-to-day-struggles. Second, it is a low-threshold approach that is easy to grasp and use.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 1 publication
1
24
0
1
Order By: Relevance
“…Likewise, labour turnover might be an expression of labour unrest in a Silverian understanding (Silver, 2003), but might also be part of the reorganisation of domination. Our findings contribute to the recent debate on the power resources approach in this journal (Gallas, 2018;Nowak, 2018;Schmalz, Ludwig and Webster, 2018). They caution against conceptualising "power" as something that can be accumulated and invested into class struggle.…”
Section: Introductionsupporting
confidence: 54%
“…Likewise, labour turnover might be an expression of labour unrest in a Silverian understanding (Silver, 2003), but might also be part of the reorganisation of domination. Our findings contribute to the recent debate on the power resources approach in this journal (Gallas, 2018;Nowak, 2018;Schmalz, Ludwig and Webster, 2018). They caution against conceptualising "power" as something that can be accumulated and invested into class struggle.…”
Section: Introductionsupporting
confidence: 54%
“…Thus, every delegation of power to a higher level by definition increases its distance from its social base, and thereby also the probability of an emergent, separate, and institutionalized self-interest. A substantial literature has shown that, in the course of the institutionalization of trade unions and parties, these institutions develop their own institutional logics which do not necessarily coincide with those they are meant to represent [90][91][92]. Thus, German trade unions are regularly conceptualized as "intermediary organizations" [93]: they mediate between capital and labor.…”
Section: The Technopolitics Of Productionmentioning
confidence: 99%
“…It is generally assumed that the major effect of digitalization on labor markets is a polarization in terms of skills[90][91][92]. The emphasis on de-skilling is not aimed at challenging this thesis but is due to the fact that the object of research was manual work, where de-skilling clearly outweighs upgrading.…”
mentioning
confidence: 99%
“…The issue of class relations leads us to an important misunderstanding of the PRA by some of the responses. In particular Gallas (2018) and Nowak (2018) perceive the PRA as a self-referential research heuristic that is largely detached from an analysis of global capitalism. At this point, it is important to clarify the intention of the PRA and to outline some of the discussions that took place a decade ago on the development of this approach.…”
Section: Areas Of Misunderstanding: Contextualising the Pramentioning
confidence: 99%
“…It is particularly striking that Nowak (2018) and Gallas (2018) both refer in their articles to labour conflicts in former German state-owned companies and state-dominated or highly regulated economic sectors (airlines and railways) in order to criticise the PRA without contextualising the cases in the larger development of German capitalism, thereby drawing a distorted picture of the role of unions in these developments. For instance, in the case of recent labour conflicts in the railway sector, marketisation has played a major role, both changing working conditions and eroding institutional power, a process German rail unions EVG and its predecessors GDA and Transnet did not vigorously challenge as they relied on a strategy of social partnership without reflecting upon the changing context.…”
Section: Areas Of Misunderstanding: Contextualising the Pramentioning
confidence: 99%